Determinants of Behavioral Intention and Use of Interactive Whiteboard by K-12 Teachers in Remote and Rural Areas - Zhou, Ying; Li, Xinxin; Wijaya, Tommy Tanu (Frontiers in Psychology, 2022)
The Interactive Whiteboard (IWB) has recently been used to replace the TWB (traditional whiteboard), with many of its features being observed to help teachers in educational activities. This is based on effectively and efficiently increasing the teacher-student interaction. Therefore, this study aims to analyze the determinants of behavioral intention (BI) and the use of interactive whiteboards by K-12 teachers, in remote and rural Chinese areas. The Modified-Unified Theory of Acceptance and Use of Technology (UTAUT2) model was used in this analysis, as a learning medium to deliver the subject matter to students. The sample and population were also the teachers in Guangxi Zhuang Autonomous Region, China, where 171 voluntary respondents participated in this study. Furthermore, the obtained data were processed using a structural equation model (SEM) approach, through the Smart-PLS software. The results showed that habit and hedonic motivation had a significant influence on the behavioral intention of teachers, towards the utilization of IWB in remote and rural areas. Besides this, facilitating conditions (FC) and BI also had a significant positive effect on usage behavior. Based on these results, important information was provided to school principals, local governments, and teachers for education quality improvement, regarding the patterns of increasing IWB utilization in remote and rural areas.